Some Global Policies for Antibiotic Resistance Depend on Legally Binding and Enforceable Commitments. (2015) - Behdinan, Asha; Hoffman, Steven J.; Pearcey, Mark
Abstract : This article assesses which policies for addressing antibiotic resistance (ABR) as part of a multi-pronged approach would benefit from legalization through an international legal agreement. Ten candidate policies were identified based on a review of existing literature, especially The Lancet Series on Antimicrobial Resistance (AMR), The Lancet Infectious Diseases Commission on AMR, and the World Health Organization (WHO) Global Action Plan for AMR. These policies were then grouped under the headings of access, conservation, and innovation. Each of the ten policies were assessed using four criteria developed by Hoffman, Røttingen, and Frenk to help consider why their legalization may be helpful, necessary and/or justified. These criteria are: (1) the problem has a significant transnational dimension; (2) the goal justifies the coercive nature of law; (3) the outcome is likely to be beneficial; and (4) legalization represents the best commitment mechanism among competing alternatives.